2015
DOI: 10.1111/nmo.12591
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin and liquid gastric emptying in children with functional dyspepsia consistent with post‐prandial distress syndrome

Abstract: FD-PDS in children is associated with lower fasting and maximum AG concentrations, and dampened AG flux. These data suggest a possible role for altered ghrelin physiology in the pathogenesis of PDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…110 Gastric accommodation is defined by the ability of the stomach to distend appropriately during a meal with an increase in gastric volume in the absence of increased gastric pressure. Gastric motility can be explored by a number of different methods (sodium acetate breath tests, 111 gastric emptying scintigraphy, 112 or electrogastrography 113 for example) and can be compared in FD and control patients in the pediatric and adult populations. Studies have shown delayed gastric emptying, 111,112 antral hypomotility, 113 and a negative correlation between gastric emptying rate and severity of abdominal pain 114 among dyspeptic patients.…”
Section: Functional Dyspepsiamentioning
confidence: 99%
See 1 more Smart Citation
“…110 Gastric accommodation is defined by the ability of the stomach to distend appropriately during a meal with an increase in gastric volume in the absence of increased gastric pressure. Gastric motility can be explored by a number of different methods (sodium acetate breath tests, 111 gastric emptying scintigraphy, 112 or electrogastrography 113 for example) and can be compared in FD and control patients in the pediatric and adult populations. Studies have shown delayed gastric emptying, 111,112 antral hypomotility, 113 and a negative correlation between gastric emptying rate and severity of abdominal pain 114 among dyspeptic patients.…”
Section: Functional Dyspepsiamentioning
confidence: 99%
“…Gastric motility can be explored by a number of different methods (sodium acetate breath tests, 111 gastric emptying scintigraphy, 112 or electrogastrography 113 for example) and can be compared in FD and control patients in the pediatric and adult populations. Studies have shown delayed gastric emptying, 111,112 antral hypomotility, 113 and a negative correlation between gastric emptying rate and severity of abdominal pain 114 among dyspeptic patients. This impaired accommodation may be linked to abnormalities of the vagal reflex and intrinsic inhibitory innervation.…”
Section: Functional Dyspepsiamentioning
confidence: 99%
“…9 One study showed altered ghrelin physiology in children with functional dyspepsia-postprandial distress syndrome during liquid meal gastric emptying study using octanoid test. 16 Another study showed no significant difference of gastric emptying between children with gastroesophageal reflux and healthy children with wide range of gastric emptying using 99Tc-DTPA-marked milk. 17 There is limited data on gastric emptying of solids and liquids following a dual-phase test meal in dyspeptic children.…”
Section: Introductionmentioning
confidence: 97%
“…Delayed liquid emptying has been demonstrated in two previous studies on youth with functional abdominal pain or FD. 14,15 One of these studies only enrolled subjects with PDS. 15 Electrogastrographic abnormalities also have been implicated in FD.…”
mentioning
confidence: 99%
“…14,15 One of these studies only enrolled subjects with PDS. 15 Electrogastrographic abnormalities also have been implicated in FD. Electrogastrography (EGG) is the technique of obtaining a cutaneous recording of gastric myoelectrical activity.…”
mentioning
confidence: 99%